1986
DOI: 10.1128/jcm.23.2.350-353.1986
|View full text |Cite
|
Sign up to set email alerts
|

Addi-Chek filtration, BACTEC, and 10-ml culture methods for recovery of microorganisms from dialysis effluent during episodes of peritonitis

Abstract: The Addi-Chek (filtration; Millipore Corp., Bedford, Mass.) and BACTEC (radiometric detection of growth in culture media; Johnston Laboratories, Inc., Towgon, Md.) systems were compared with the 10-mi culture (centrifugation) method for the recovery of microorganisms from peritoneal dialysate collected from patients with clinical evidence of peritonitis and containing 2200 leukocytes per mm3. Both alternate methods were comparable, and results were not significantly different from those of the conventional 10-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
28
0

Year Published

1986
1986
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 8 publications
1
28
0
Order By: Relevance
“…Several studies have shown that culture rates increased significantly with the BACTEC blood culture system compared with conventional culture systems [3,5,9,12]. In our study, we also found that the BACTEC blood culture system increased the culture positivity (73/127) compared with direct inoculation of the centrifuged deposit of fluid into different culture media (63/127).…”
supporting
confidence: 74%
See 1 more Smart Citation
“…Several studies have shown that culture rates increased significantly with the BACTEC blood culture system compared with conventional culture systems [3,5,9,12]. In our study, we also found that the BACTEC blood culture system increased the culture positivity (73/127) compared with direct inoculation of the centrifuged deposit of fluid into different culture media (63/127).…”
supporting
confidence: 74%
“…The low culture positivity in patients with peritonitis on CAPD has been attributed to the low load of the organisms in the majority of the patients, the presence of an antimicrobial agent in the peritoneal fluid of the patient receiving antimicrobial therapy, the presence of intracellular organisms, peritonitis caused by endotoxin released by bacterial infection and the culture technique used for the isolation of the organism [9]. Different investigators have used several methods to enhance the yield of organisms from the CAPD effluent, including the use of mass spectroscopy and sequencing and MALDI-TOF [3][4][5][6][7][8][9][10][11]. In the present study, we have observed high culture positivity with water lysis specimens and specimens pretreated with Triton-X and Tween-80 incorporated blood agar when compared with the automated blood culture system and direct inoculation of the centrifuged deposit of the specimen into different culture media.…”
mentioning
confidence: 99%
“…Generally, the larger the volume of effluent cultured, the higher the detection rates. However, comparative studies indicate that the minimum volume that should be tested is 10 ml (5,13,15,21). The method chosen should include an enrichment broth with antiphagocytic and lytic properties (3,18,19).…”
mentioning
confidence: 99%
“…The method chosen should include an enrichment broth with antiphagocytic and lytic properties (3,18,19). Both centrifugation (12,13,20) and filtration (11)(12)(13)(14)20) have been tested as means of concentrating bacteria from CAPD effluents. Semiautomated blood culture systems have been used for the detection of peritonitis in CAPD effluents.…”
mentioning
confidence: 99%
“…Numerous studies have documented the advantage of using blood-culture bottle kits to improve the microbial yield of peritoneal fluid culture [2,[4][5][6][7][8][9]. The widely used BacT/AlerT In this study, we evaluated the performance of inoculation and culture of PD effluent using FAN Plus blood culture media.…”
Section: Introductionmentioning
confidence: 99%